2009
DOI: 10.1002/oa.1059
|View full text |Cite
|
Sign up to set email alerts
|

A possible case of an ossifying fibroma in a Late Neolithic population from Portugal

Abstract: This paper discusses the differential diagnosis of an unusual bone tumour observed in the right maxilla of one adult calvarium, from the Late Neolithic collective burial of Lapa do Bugio (Sesimbra, Portugal). The differential diagnosis of the lesion gave rise to several possible pathological conditions, namely, ossifying fibroma, fibrous dysplasia, and focal cemento‐osseous dysplasia. Despite the impossibility of performing histological analysis, various macroscopic and radiological aspects lead us to consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Two bioarchaeological case studies with osseous lesions in the maxillary sinus from Portugal (3710–3620 BC , Silva & Wasterlain, ) and Spain (sixth–seventh centuries AD; Colard et al, ), both of which have been identified as COF, bear clear macroscopic similarities with the case presented here. As a rule, COFs (ICD‐O code: 9262/0) are monostotic unilocular tumours (Baumhoer, ; MacDonald, ; Slootweg & El Mofty, ) that can reach considerable proportions and cause significant functional and cosmetic problems (Agarwal, Kumar, Singh, & Usmani, ; Kuta, Worley, & Kaugars, ; Lawson et al, ).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Two bioarchaeological case studies with osseous lesions in the maxillary sinus from Portugal (3710–3620 BC , Silva & Wasterlain, ) and Spain (sixth–seventh centuries AD; Colard et al, ), both of which have been identified as COF, bear clear macroscopic similarities with the case presented here. As a rule, COFs (ICD‐O code: 9262/0) are monostotic unilocular tumours (Baumhoer, ; MacDonald, ; Slootweg & El Mofty, ) that can reach considerable proportions and cause significant functional and cosmetic problems (Agarwal, Kumar, Singh, & Usmani, ; Kuta, Worley, & Kaugars, ; Lawson et al, ).…”
Section: Discussionsupporting
confidence: 69%
“…Bone tumours or tumour-like lesions in the areas of the face and jaws have often been identified in archaeological skeletal remains (Bartelink & Wright, 2011;Colard, Gabart, & Blondiaux, 2008;Gresky, Kalmykov, & Berezina, 2018;Silva & Wasterlain, 2010). Establishing a diagnosis, however, is a complex task; macroscopic assessment is therefore not sufficient, and radiological or histopathological analyses are required even in archaeological specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In 1964, Agostinho Isidoro published some data about the human bones uncovered from Lapa do Bugio, but since then these specimens received no further scholarly attention until the late 1990s (Silva and Marques, 2009;Silva and Wasterlain, 2010).…”
Section: Anthropological Datamentioning
confidence: 99%
“…Although they may contain a varying quantity of calcified, bone-resembling tissue, like osteomas and osteoblastomas, ossifying fibromas are generally well-defined in radiolucency and are regularly organised (Fu and Perzin, 1976;Liu et al, 2010;Pogrel et al, 2005). A proliferative lesion within the maxillary sinus of a Late Neolithic adult has been recently described and proposed to be ossifying fibroma (Silva and Wasterlain, 2010), a rare case within the published archaeological literature. The morphological and radiographic dissimilarities of SK611's lesion to this, or any of the potential benign or malignant neoplasms known to affect the maxilla or paranasal sinuses, make them an unlikely primary cause.…”
Section: Discussionmentioning
confidence: 99%
“…Histological evidence may add confidence to a differential diagnosis where microscopic features are pathognomonic, but it is rarely possible to reach a definitive diagnosis based on histopathology alone, due to the similarity of histological features between distinct diagnostic entities (Eversole et al, 2008;Silva and Wasterlain, 2010). With this constraint in mind, a differential diagnosis was attempted based upon macroscopic, radiographic, and CBCT evidence.…”
Section: Methodsmentioning
confidence: 99%